Penggunaan Media Gambar Terhadap Hasil Belajar Mata Pelajaran Pendidikan Agama Islam di SD Negeri 1 Tamanwinangun - Dwinanda Suluh Phangesti; Imam Subarkah; Maryanto Maryanto (IAINU Kebumen, 2023)
The purpose of this study was to determine the use of image media in Islamic Religious Education (PAI) learning for sixth grade students of SD Negeri 1 Tamanwinangun. The method used is a quantitative research approach and the type of research conducted is experimental. The design used was a one-group pretest-posttest. Data collection techniques using pretest-posttest tests, questionnaires, interviews, documentation and observation. Hypothesis testing using paired sample t test. The results showed that the use of image media gave a good impression on students and had a positive effect on student learning in grade VI Islamic Religious Education subjects at SD Negeri 1 Tamanwinangun in the 2021/2022 academic year, in general it could improve student learning outcomes with the following results: (a) The average score of students at the pretest was 6.67 and at the posttest was 8.72 (b) students' learning mastery also increased, at the pretest it was 40.7% to 96.3% at the posttest.